Evaluating the Zones of Regulation® intervention to improve the self-control of elementary students - Stephanie Ochocki; Andy J. Frey; David A. Patterson; Freida Herron; Natalie Beck; David R. Dupper (International Journal of School Social Work, 2020)
School social workers provide social, emotional, and behavioral interventions for elementary-age students within multi-tiered systems of support (MTSS) when disruptive behavior and deficits in self-control are observed. Secondary/Tier 2 cognitive- and behaviorally-oriented interventions that target self-control have been shown to impact positive outcomes in academic, social, emotional, and behavioral realms for elementary-age students. This study sought to evaluate the Zones of Regulation® intervention for elementary-age students identified with disruptive behavior via a small randomized controlled trial (N = 63). Students were identified for disruptive behavior concerns through a universal behavior screening process and were randomly assigned to the intervention group or the control group. School social workers utilized twelve selected lessons from the cognitive-behaviorally oriented Zones of Regulation® curriculum sequence for a six-week Secondary/Tier 2 group intervention. Implementation of the Zones of Regulation® curriculum did not result in statistically significant decreases in students’ disruptive behavior or improve their self-control. More tailored efforts to explore the social validity and effectiveness of the Zones® within MTSS school structures is warranted given the widespread use of the curriculum by school social workers and other specialized instructional support personnel.
Keywords: children; disruptive behavior; elementary-age; multi-tiered interventions; school; school social work; Secondary/Tier 2 interventions; self-control; Zones of Regulation®